A Review on Factors Influencing the Fermentation Process of Teff (Eragrostis teff) and Other Cereal-Based Ethiopian Injera. (24th March 2022) - Mengesha, Yizengaw; Tebeje, Alemu; Tilahun, Belay
Abstract : Fermented foods and beverages are the product of the enzymaticcally transformed food components which are acived by different microorganisms. Fermented foods have grown in popularity in recent years because of their alleged health benefits. Biogenic amines, bioactive peptides, antinutrient reduction, and polyphenol conversion to physiologically active chemicals are all possible health benefits of fermentation process products. In Ethiopian-fermented foods, which are mostly processed using spontaneous fermentation process. Injera is one of the fermented food products consumed in all corners of the country which sourdough fermentation could be achieved using different LAB and yeast strains. Moreover, the kind and concentration of the substrate and the type of microbial flora, as well as temperature, air supply, and pH, all influence the fermentation process of injera. This review article gives an overview of factors influencing the fermentation process of teff ('Eragrostis tef.') and other cereal-based Ethiopian injera.